The need to achieve: Players' perceptions and uses of extrinsic meta-game reward systems for video game consoles. (June 2017) - Cruz, Carlos; Hanus, Michael D.; Fox, Jesse
Abstract: Microsoft's Xbox and Sony's PlayStation overlay achievement and trophy systems onto their video games. Though these meta-game reward systems are growing in popularity, little research has examined whether players notice, use, or seek out these systems. In this study, game players participated in focus groups to discuss the advantages and disadvantages of meta-game reward systems. Participants described the value of meta-game reward systems in promoting different ways to play games, giving positive feedback about game play, and boosting self-esteem and online and offline social status. Participants discussed completionists, or gamers that want to earn all of the badges associated with the meta-game. Though self-determination theory and its subtheory cognitive evaluation theory suggest that extrinsic rewards might harm players' intrinsic motivation, our findings suggest players may see these systems as intrinsically motivating in this context. The implications of rewards systems for motivation, video game habits, and internet gaming disorder are discussed. Highlights: Focus groups were conducted to explore gamer perceptions of meta-game rewards. Some gamers indicated they felt compelled to earn all of the rewards available. Social comparison emerged as a key theme related to ego maintenance and boosting. Players were divided on whether earned badges indicate skill or time. Badges are capable of disrupting engagement in the game.